2022
DOI: 10.1186/s40793-022-00424-2
|View full text |Cite
|
Sign up to set email alerts
|

In-depth characterization of denitrifier communities across different soil ecosystems in the tundra

Abstract: Background In contrast to earlier assumptions, there is now mounting evidence for the role of tundra soils as important sources of the greenhouse gas nitrous oxide (N2O). However, the microorganisms involved in the cycling of N2O in this system remain largely uncharacterized. Since tundra soils are variable sources and sinks of N2O, we aimed at investigating differences in community structure across different soil ecosystems in the tundra. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 100 publications
1
28
0
Order By: Relevance
“…Indeed, annotation of protein-coding genes revealed that the two Obscuribacterales MAGs do not appear to encode proteins of the Calvin cycle (Rbc), photosystems I and II (Psa and Psb), cytochrome b6f complex (Pet), or phycobilisomes (Apc, Cpc, Cpe, and Pec) (). Interestingly, the presence of genes for the small and large subunits of nitric oxide reductase (NorC and NorB, respectively) indicates a potential role of this lineage in the production of the greenhouse gas nitrous oxide [37].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, annotation of protein-coding genes revealed that the two Obscuribacterales MAGs do not appear to encode proteins of the Calvin cycle (Rbc), photosystems I and II (Psa and Psb), cytochrome b6f complex (Pet), or phycobilisomes (Apc, Cpc, Cpe, and Pec) (). Interestingly, the presence of genes for the small and large subunits of nitric oxide reductase (NorC and NorB, respectively) indicates a potential role of this lineage in the production of the greenhouse gas nitrous oxide [37].…”
Section: Resultsmentioning
confidence: 99%
“…3). Interestingly, the presence of genes for the small and large subunits of nitric oxide reductase (NorC and NorB, respectively) indicates a potential role of this lineage in the production of the greenhouse gas nitrous oxide [37].…”
Section: Recovery Of Cyanobacterial Genomes From Metagenomic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Siderophilus nitratireducens ”, encoded the genes for iron oxidation (cytochrome c cyc2 ) and the periplasmic nitrate reductase ( nap ), thereby supporting the hypothesis of nitrate-driven iron oxidation being its primary metabolism under the restricted availability of alternative substrates. The absence of other denitrification genes suggests a short catabolic path, which might offer a kinetic advantage in terms of higher iron oxidation rates (21) especially under N limitation (22). “ Ca.…”
Section: Discussionmentioning
confidence: 99%